Towards geographies of child protection. Issue 12 (20th September 2020) - Disney, Tom; Lloyd, Jenny
Abstract: The emergence of current and historic cases of child abuse across the globe has, in recent years, dominated the news, political agendas and popular discourse surrounding children. From serious case reviews to exploitation in post‐conflict zones, from sexual abuse of children by groups to trafficking of drugs across countries, the importance of protecting children is an increasing concern in many countries. Key to, and inherent in, all of these processes and phenomena are child protection systems, working in varying degrees of effectiveness. While geographic interest has touched upon many of these areas, the role of child protection systems, and the practitioners that work within these, do not explicitly feature within this work. In this article, we seek to develop an introduction to geographies of child protection, producing an initial critical review which points to future research avenues in this field. We adopt a Foucauldian approach and review four themes to illustrate the ways in which geographical approaches might yield important insights. Drawing primarily on England as a context, we consider the historical geographies and origins of child protection, relational practices in contemporary child protection, the impact of austerity and finally we consider what future directions might require a geographical approach.